2020
DOI: 10.11604/pamj.supp.2020.35.2.23910
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: challenges affecting the uptake of e-learning in pharmacy education in Africa

Abstract: The effort by countries and relevant stakeholders to improving the quality of pharmacy education globally is being countered by the outbreak of infectious diseases. In order to curtail the spread of the coronavirus, unprecedented measures such as total/partial lockdowns and ban on public gatherings have been put in place by several governments. These measures implemented have put a halt on academic activities and schooling and have invariably affected the delivery of pharmacy education globally and Africa is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 7 publications
0
43
0
Order By: Relevance
“…26 In contrast, when some basic infrastructure represents a concern, distance education might be a challenging process. 21 , 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In contrast, when some basic infrastructure represents a concern, distance education might be a challenging process. 21 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…26 In contrast, when some basic infrastructure represents a concern, distance education might be a challenging process. 21,27 After having participants' views on the readiness to the shift to distance education, an important issue was how they generally perceived distance education after the experience they went through. Participants' perception toward distance education was generally positive.…”
mentioning
confidence: 99%
“…It is worth mentioning that almost half of the students preferred to continue traditional face to face teaching over distance learning and hybrid teaching styles. This finding was attributed to the fact that students have barriers to technology, and the majority of them do not have the luxury of quiet space at home with stable electricity and internet connection (Okereke et al, 2020). The current student's technology resources are not sufficient to start online education due to the fact that wireless internet connection is still a challenge in many African countries including Sudan (Okereke et al, 2020).…”
Section: Impact Of Covid-19 On Pharmacy Students In Sudanmentioning
confidence: 99%
“…However, many low-and lower-middle income countries (LMIC) struggle with e-learning due to challenges with infrastructure, resource availability, communication, and social barriers (9). A recent review of the transition to e-learning in pharmacy schools in Africa found numerous barriers related to poor accessibility in rural areas, high cost of internet data, and poor infrastructure in many areas (10,11). Furthermore, students are likely to face new challenges in the learning environment.…”
Section: Introductionmentioning
confidence: 99%